The Correlation between Posyandu Compliance and Feeding Patterns with Stunting Incidence in The Working Area of Puskesmas Kerek Tuban East Java, Indonesia - Nur Maziyah, Hurin'in; Miftahul, Munir; Aris Puji, Utami; Sholafatul, Ulfania (Journal of health research and technology, 2023)
Stunting is associated with an increased risk of morbidity and mortality as well as retarded motor and mental growth. The research design uses a correlational research method with a cross-sectional approach. This study to know the correlation Between Posyandu Compliance and Feeding Patterns with Stunting Incidents in Toddlers in the Working Area of the Kerek Health Center, Kerek District, Tuban Regency. This type of research is a correlational study with a cross-sectional approach. The population in this study were mothers and toddlers who came to Posyandu in the working area of the Puskesmas, Kerek District, Tuban Regency. Respondents in this study were 30 respondents who were taken by purposive sampling technique. The independent variable in this study was posyandu compliance and feeding patterns and the dependent variable in this study was stunting in toddlers. Data collection using the Child Feeding Questionnaire (CFQ) and KMS toddlers and toddlers' height was measured using a microtoise and converted into a standard Z-score. The results of research conducted on 30 respondents. Then the data were analyzed using the Spearmen's Rho test with a significance level of α = 0.05. The results of this study showed that there was a significant correlation between posyandu compliance with p-value 001 < 0.005 and feeding patterns with the incidence of stunting in toddlers aged 12-24 months with p-value 001 < 0.005. It was concluded that there was a correlation between posyandu compliance and the feeding pattern of stunted toddlers